2017
DOI: 10.1016/j.cca.2017.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Equal clinical performance of a novel point-of-care cardiac troponin I (cTnI) assay with a commonly used high-sensitivity cTnI assay

Abstract: The Minicare cTnI POC assay may become useful for prompt and safe ruling-out of AMI in ED patients with suspected AMI using a guideline supported 0/3h sampling protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…During myocardial ischemia, the membranes of cardiac muscle cells were damaged, leading to the release of myocardial enzymes and proteins including cTnI, cTnT, LDH, and Mb into peripheral blood. Therefore, detecting the levels of cTnI, cTnT, LDH, and Mb in peripheral blood can reflect the degree of myocardial ischemia necrosis 29. In our study, we observed that GB treatment downregulated the high levels of cTnI, cTnT, LDH, and Mb and also improved the damaged myocardial cells induced by I/R injury significantly, indicating that GB mitigated myocardial injury in myocardial I/R model rats.…”
Section: Discussionsupporting
confidence: 54%
“…During myocardial ischemia, the membranes of cardiac muscle cells were damaged, leading to the release of myocardial enzymes and proteins including cTnI, cTnT, LDH, and Mb into peripheral blood. Therefore, detecting the levels of cTnI, cTnT, LDH, and Mb in peripheral blood can reflect the degree of myocardial ischemia necrosis 29. In our study, we observed that GB treatment downregulated the high levels of cTnI, cTnT, LDH, and Mb and also improved the damaged myocardial cells induced by I/R injury significantly, indicating that GB mitigated myocardial injury in myocardial I/R model rats.…”
Section: Discussionsupporting
confidence: 54%
“…High myocardial specificity was required to detect the indexes of cTnI and cTnT and high sensitivity to determine the index of Mb in myocardial ischemic necrosis [ 26 ]. During myocardial ischemia, the integrity of the cardiac muscle cell membranes is damaged, causing myocardial enzymes and proteins, such as Mb, cTnI and cTnT, to be released into the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…However, a 90.5% sensitivity and 94.4% NPV may be adequate for the purpose of triaging patients to a referral hospital based on a low-risk assessment. Furthermore, our data from the core-lab-PMHP suggests that as newer, more sensitive, POC cTn assays become available in the US, the sensitivity of the PMHP will improve [27,28]. In fact, in this cohort the core-lab-PMHP (the combination of a HEAR score with a core lab cTn measure from prehospital blood) achieved 100% sensitivity and NPV for 30-day MACE.…”
Section: Plos Onementioning
confidence: 84%